2022
DOI: 10.3847/1538-4357/ac75eb
|View full text |Cite
|
Sign up to set email alerts
|

SN 2016dsg: A Thermonuclear Explosion Involving a Thick Helium Shell

Abstract: A thermonuclear explosion triggered by a He-shell detonation on a carbon–oxygen white-dwarf core has been predicted to have strong UV line blanketing at early times due to the iron-group elements produced during He-shell burning. We present the photometric and spectroscopic observations of SN 2016dsg, a subluminous peculiar Type I supernova consistent with a thermonuclear explosion involving a thick He shell. With a redshift of 0.04, the i-band peak absolute magnitude is derived to be around −17.5. The object … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…These events are faint, red, and show strong line-blanketing in spectra at maximum light. A tentative detection of unburnt helium in SN 2016dsg was also reported by Dong et al (2022a). We refer to these events as peculiar He-shell DDet SNe.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…These events are faint, red, and show strong line-blanketing in spectra at maximum light. A tentative detection of unburnt helium in SN 2016dsg was also reported by Dong et al (2022a). We refer to these events as peculiar He-shell DDet SNe.…”
Section: Introductionsupporting
confidence: 65%
“…SN 2019ofm has a large projected offset (∼11 kpc) but is still on a spiral arm, as shown in its DECaLS image (Dey et al 2019). Other objects, including the recently reported SN 2016dsg and OGLE-2013-SN-079 (Dong et al 2022a), show large projected host offsets (10 kpc) and lie in the galaxy outskirts, which usually indicates an old stellar population origin.…”
Section: The Host Environment Of He-shell Ddet Snementioning
confidence: 84%
See 2 more Smart Citations
“…Similarly Shen et al (2021b) found that their minimal He shell mass models were able to reproduce normal SNe Ia. Double detonation models have been suggested to explain a number of peculiar SNe Ia (Inserra et al 2015;Jiang et al 2017;De et al 2019;Dong et al 2022), which showed unusually red colours, early flux excesses and Ti absorption features. The red colours can be explained by absorption at blue wavelengths by the products of the helium shell detonation, as can the Ti absorption features (e.g.…”
Section: Introductionmentioning
confidence: 95%